A critical analysis of the proportionality test in human rights adjudication - Urbina, F; Francisco Urbina (2013)
In this thesis I argue against the proportionality test in human rights adjudication, and provide a framework for understanding the proportionality debate. I identify two accounts of proportionality. One sees proportionality as a doctrinal tool aimed at maximising rights and public interests. The other sees proportionality as allowing for open- ended moral reasoning. I analyse the two accounts and identify their main deficiencies. I argue against both conceptions, and conclude that defenders of proportionality are in the following dilemma: either proportionality is insensitive to important moral considerations related to human rights and their limitations, and thus it is an unsuitable tool for human rights adjudication; or proportionality can accommodate the relevant moral considerations, but at the price of leaving the judge undirected, unaided by the law. I will further argue that lack of guidance is a deficiency in legal adjudication, which has important negative effects.